2021
DOI: 10.5098/hmt.16.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MHD Flow and Heat Transfer of Laminar Flow Between Porous Disks

Abstract: A study is carried out for the two dimensional laminar flow of conducting fluid in presence of magnetic field. The governing non-linear equations of motion are transformed in to dimensionaless form. A solution is obtained by homotopy perturbation method and it is valid for moderately large Reynolds numbers for injection at the wall. Also an efficient algorithm based finite difference scheme is developed to solve the reduced coupled ordinary differential equations with necessary boundary conditions. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The study made by Khaled and Vafai (2003) showed the importance of porous media in modeling flow and heat transfer. Many authors have contributed to the study of porous media [Rees and Pop (2000); Badruddin et al (2020); Pai et al (2021)].…”
Section: Introductionmentioning
confidence: 99%
“…The study made by Khaled and Vafai (2003) showed the importance of porous media in modeling flow and heat transfer. Many authors have contributed to the study of porous media [Rees and Pop (2000); Badruddin et al (2020); Pai et al (2021)].…”
Section: Introductionmentioning
confidence: 99%
“…El-Amin (2003) has studied the effect of MHD forced convection over a non-isothermal horizontal cylinder embedded in a fluid-saturated porous medium. Nagaraju et al (2019); Kumar et al (2021) analyzed the MHD flow and heat transfer with geometries of the circular horizontal pipe and porous disks, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Free convection or natural convection is the flow induced by buoyancy forces that arise from density differences caused by temperature variation in the fluid [11]. Nowadays, many researchers have investigated the problem in fluid flow in either Newtonian or non-Newtonian fluid [12][13][14][15][16][17][18][19]. Among them, few have considered free convection flow on second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%